An Assessment of Practicing Reflection in Teaching the Concepts for Engineering Statics - Ande S. (Civil Engineering Dimension, 2011)
This paper shares the experience of Dr Ande in practicing reflection in teaching the concepts for Engineering Statics. His constant pursuit of being a reflective practitioner has made him more evolved as an effective teacher and made him more flexible in modifying his practice. It is interesting to learn from Dr. Ande experience.